The divorce referendum 2019 - Keenan, Lisa (My University, 2020)
When Ireland removed the prohibition on divorce from its constitution in 1995 by way of a referendum, the result was achieved with a razor thin margin after a difficult campaign. The circumstances in which the 2019 referendum on divorce took place were very different. After the hotly contested marriage equality and abortion referendums, a proposal to liberalise the divorce regime by removing the paragraph relating to the mandatory separation period from the constitution, and to enact legislation to halve that period, was uncontroversial. The amendment received widespread support from both the public and the political elite. The campaign was muted and largely overshadowed by the local and European elections that were taking place at the same time. On 24 May 2019, 82 per cent of the electorate voted in favour of the Thirty-Eighth Amendment. This result can be seen as another step in the ongoing project to modernise the Irish constitution.
PUBLISHED
https://doi.org/10.1080/07907184.2019.1652167
Keywords: Referendum; Divorce; Irish politics; Marriage; Family rights; Irish Politics; Irish politics, election study, electoral behaviour; Referendums